Intraday renewable electricity trading: advanced modeling and numerical optimal control - Glas, Silke; Kiesel, Rüdiger; Kolkmann, Sven; Kremer, Marcel; Graf von Luckner, Nikolaus; Ostmeier, Lars; Urban, Karsten; Weber, Christoph (Journal of mathematics in industry, 2020)
As an extension of (Progress in industrial mathematics at ECMI 2018, pp. 469–475, 2019 ), this paper is concerned with a new mathematical model for intraday electricity trading involving both renewable and conventional generation. The model allows to incorporate market data e.g. for half-spread and immediate price impact. The optimal trading and generation strategy of an agent is derived as the viscosity solution of a second-order Hamilton–Jacobi–Bellman (HJB) equation for which no closed-form solution can be given. We construct a numerical approximation allowing us to use continuous input data. Numerical results for a portfolio consisting of three conventional units and wind power are provided.